2014
DOI: 10.1159/000363129
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Cardioembolic Stroke Including Paradoxical Brain Embolism in Patients with Acute Ischemic Stroke before and after the Great East Japan Earthquake

Abstract: Background: The incidence of heart disease or deep vein thrombosis (DVT) reportedly increased after the Great East Japan Earthquake. We hypothesized that the incidence of cardioembolic stroke (CES) including paradoxical brain embolism (PBE) among patients with acute stroke would increase after the earthquake due to cessation of antithrombotic therapy or the increase in heart disease and DVT associated with the evacuation. The aim of this study is to evaluate the changes in the prevalence of DVT and the inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…In the three months following the Hanshin-Awaji Earthquake in 1995, the incidences of coronary heart disease and stroke events increased by 50% and 90%, respectively [4]. A recent observational study reported that a significant increase in the incidence of cardioembolic stroke occurred after the Great East Japan Earthquake, compared with the period before the earthquake [19]. Interestingly, the study found more cases of paradoxical brain embolism and deep vein thrombosis associated with evacuation in the period three to twelve months after the earthquake.…”
Section: Discussionmentioning
confidence: 99%
“…In the three months following the Hanshin-Awaji Earthquake in 1995, the incidences of coronary heart disease and stroke events increased by 50% and 90%, respectively [4]. A recent observational study reported that a significant increase in the incidence of cardioembolic stroke occurred after the Great East Japan Earthquake, compared with the period before the earthquake [19]. Interestingly, the study found more cases of paradoxical brain embolism and deep vein thrombosis associated with evacuation in the period three to twelve months after the earthquake.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown the short-term influence of the Great East Japan Earthquake and tsunami disaster on increases in emergency department visits and hospital admissions due to cardiovascular disease,9 10 cerebrovascular disease,9 11 respiratory disease,9 12–14 infectious disease,15 gastrointestinal bleeding16 and others 9 17. However, it remains unknown whether the earthquake and tsunami disaster affected long-term health conditions of people in the affected areas.…”
Section: Introductionmentioning
confidence: 99%
“…Further, an increase in the number of individuals with acute myocardial infarction, especially women, was particularly evident during the 4 weeks immediately following the disaster. 9 After the Great East Japan Earthquake, the incidence of reported cardioembolic stroke increased in the 3-9 months following the disaster, 10 as did the incidence of other cardiovascular diseases. [11][12][13][14] Our study contributes to the reported incidence of cardiovascular disease using self-report questionnaires rather than death certificates and by demonstrating that exacerbated cardiovascular symptoms occurred among evacuees after the disaster.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14] A recent study reported a heterogeneous occurrence of cardiovascular events after the Great East Japan Earthquake, 2 while another study reported a significant increase in the incidence of cardioembolic stroke after the earthquake. 10 However, neither study examined the incidence of perceived cardiovascular disease symptoms after a disaster, nor did they focus on the effect of refugee socioeconomic status on health problems during the evacuation period. Yet these aspects should be considered because they are relevant for reviewing refugee health status, assessing the incidence of various diseases and providing health guidelines for refugees.…”
Section: Introductionmentioning
confidence: 99%